A Methodology for Introducing Competitive Anxiety and Pressure in VR Sports Training - Argelaguet Sanz, Ferran; Multon, Franck; Lécuyer, Anatole (Frontiers in Robotics and AI, 2015)
Athletes' performances are influenced by internal and external factors, including their psychological state and environmental factors, especially during competition. As a consequence, current training programs include stress management. In this paper, we explore whether highly immersive systems can be used for such training programs. First, we propose methodological guidelines to design sport training scenarios both on considering the elements that a training routine must have, and how external factors might influence the participant. The proposed guidelines are based on Flow and social-evaluative threat theories. Second, to illustrate and validate our methodology, we designed an experimental setup reproducing a ten meter Olympic pistol shooting. We analyzed whether changes in the environment are able to induce changes in user performance, physiological responses and the subjective perception of the task. The simulation included stressors in order to raise a social-evaluative threat, such as aggressive public behavior or unforced errors, increasing the pressure while performing the task. The results showed significant differences in their subjective impressions, trends in the behavioral and physiological data were also observed. Taken together, our results suggest that highly immersive systems could be further used for training in sports.